The effects of baicalein or baicalin on the colloidal stability of ZnO nanoparticles (NPs) and toxicity of NPs to Caco-2 cells. (24th March 2018) - Li, Yining; Zhang, Cao; Liu, Liangliang; Gong, Yu; Xie, Yixi; Cao, Yi
Abstract: Recent study suggested that the presence of phytochemicals in food could interact with nanoparticles (NPs) and consequently reduce the toxicity of NPs, which has been attributed to the antioxidant properties of phytochemicals. In this study, we investigated the interactions between ZnO NPs and two flavonoids baicalein (Ba) or baicalin (Bn) as well as the influence of the interactions on the toxicity of ZnO NPs to Caco-2 cells. The antioxidant properties of Ba and Bn were confirmed by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assays, with Ba being stronger. However, the presence of Ba or Bn did not significantly affect cytotoxicity, intracellular superoxide or release of inflammatory cytokines of Caco-2 cells after ZnO NP exposure. When Ba was present, the cellular viability of Caco-2 cells after exposure to ZnO NPs was slightly increased, associated with a modest decrease of intracellular Zn ions, but these effects were not statistically different. Ba was more effective than Bn at changing the hydrodynamic sizes, Zeta potential and UV–Vis spectra of ZnO NPs, which indicated that Ba might increase the colloidal stability of NPs. Taken together, the results of the present study indicated that the anti-oxidative phytochemical Ba might only modestly protected Caco-2 cells from the exposure to ZnO NPs associated with an insignificant reduction of the accumulation of intracellular Zn ions. These results also indicated that when assessing the combined effects of NPs and phytochemicals to cells lining gastrointestinal tract, it might be necessary to evaluate the changes of colloidal stability of NPs altered by phytochemicals.